Analisis Peran Supervisi Akademik Kepala Sekolah Kepada Guru IPA DI SMP Negeri 20 Kupang - Saldi Salmun Ballu; Lukas Manu; Agus Maramba Meha (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
One important element in the implementation of education is the principal, who has the task of supervising and fostering the pattern of ongoing teaching activities, for example supervising all teachers in schools to help improve the quality of learning and the performance of a teacher. Often teachers experience various obstacles, which can arise from various factors so that the learning process is less than optimal. Therefore, the principal needs to provide academic supervision to help develop teacher competence and professionalism. The purpose of this study was to determine how the principal's academic supervision of science teachers at SMP Negeri 20 Kupang and the constraints in implementing academic supervision. The approach used is qualitative. Data collection techniques are observation, interviews, documentation, and questionnaires. The data were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the principal's academic supervision of the teacher had been carried out well, the principal had planned by preparing the supervision instrument and informing the schedule of supervision, the implementation of supervision using various techniques and principles. Evaluation and follow-up of academic supervision are carried out by discussing the results of supervision with the teacher, the school also holding workshops/training to improve and improve the quality of teachers in carrying out their duties at school. the implementation of academic supervision experiences obstacles that arise from the teacher, namely the lack of preparation of learning devices, the teacher does not master the material during the learning process and the teacher does not master the class, where it seems that students are difficult to control in the learning process.